Genome sequence of an unclassified pleosporales species isolated from human nasopharyngeal aspirate - Ng, Kee Peng; Yew, Su Mei; Chan, Chai Ling; Tuck Soon, S.H.; Shiang, L.N.; Hassan, Hamimah; Ngeow, Yun Fong; Chee, Choong Hoh; Kok, W.L.; Wai, Y.Y. (2012)
Pleosporales is the largest order in the fungal class Dothideomycetes. We report the 36,814,818-bp draft genome sequence and gene annotation of UM1110, a Pleosporales isolate associated with unclassified genera that is potentially a new fungal species. Analysis of the genome sequence led to the finding of genes associated with fungal adhesive proteins, secreted proteases, allergens, and pseudohyphal development.